Legal Pluralism and Indigenous Rights: The Case of the Indigenous Forest People of Jambi, Indonesia - Robi Awaludin; Zuhraini Zuhraini; Nurnazli Nurnazli (Rule of Law Studies Journal, 2025)
Background:Numerous indigenous groups in Indonesia, including the Orang Rimba (Suku Anak Dalam) in Jambi Province, experience challenges in asserting their traditional land rights. The expansion of government and private land use frequently triggers conflicts, highlighting a gap between customary practices and formal legal systems. Aims: This research explores the legal protection afforded to the Orang Rimba, with a focus on how their customary laws interact with Indonesia’s national legislation. It also aims to assess whether these indigenous rights receive effective legal acknowledgment and protection. Methods: Using a qualitative descriptive method, the study applies normative legal analysis and incorporates field-based case observations. Data were obtained through the examination of relevant legal documents, statutory regulations, and localized field insights from affected communities. Result: Results indicate that although Indonesia recognizes indigenous law in principle, its application remains inconsistent. The Orang Rimba often find their land rights excluded from formal legal decisions, resulting in continuous marginalization. State-centric legal mechanisms still dominate, with little room for the integration of customary systems. Conclusion: This case reflects a critical need for reinforcing indigenous legal recognition in Indonesia. Integrating customary law into the broader legal structure is vital to ensuring justice and safeguarding the rights of traditional communities facing land tenure insecurity.